The Impact of Organizational Digital Transformation and HR Technology Adoption on Employee Performance at PT PAL Indonesia - Anggraini, Mike Dian; Rahayu, Sri; Sundjoto, Sundjoto; Fitrianty, Rifda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the impact of organizational digital transformation and HR technology adoption on employee performance at PT PAL Indonesia, a state-owned enterprise operating in the maritime defense manufacturing sector. Using a quantitative explanatory approach, this research adopts a census design involving all 1,444 permanent employees as respondents. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression with SPSS. The results demonstrate that organizational digital transformation has a positive and significant effect on employee performance, indicating that digitalized infrastructure, integrated systems, leadership support, and a supportive digital culture enhance employees’ productivity, work quality, and adaptability. In addition, HR technology adoption reflected in the use of human capital management systems, e-learning platforms, and digital performance management tools also shows a positive and significant influence on employee performance. Simultaneous testing confirms that both variables jointly form a coherent system that significantly explains variations in employee performance. The regression model exhibits strong explanatory power, with an R² value of 0.657, indicating that 65.7% of employee performance variance is explained by the model. These findings highlight that digital transformation yields optimal performance outcomes when supported by active employee adoption of HR technologies. The study contributes to the digital human resource management literature by providing empirical evidence from a large, labor-intensive manufacturing SOE context and offers practical insights for organizations seeking to implement human-centered digital transformation strategies to enhance sustainable employee performance.